Adrenomedullin2 stimulates progression of thyroid cancer in mice and humans under nutrient excess conditions. Issue 3 (13th September 2022) - Kim, Jung Tae; Lim, Mi Ae; Lee, Seong Eun; Kim, Hyun Jung; Koh, Hyun Yong; Lee, Jeong Ho; Jun, Sang Mi; Kim, Jin Man; Kim, Kun Ho; Shin, Hyo Shik; Cho, Sun Wook; Kim, Koon Soon; et al.
Abstract: Thyroid cancer is associated with genetic alterations, e.g. BRAF V600E, which may cause carcinomatous changes in hormone‐secreting epithelial cells. Epidemiological studies have shown that overnutrition is related to the development and progression of cancer. In this study, we attempted to identify the cell nonautonomous factor responsible for the progression of BRAF V600E thyroid cancer under overnutrition conditions. We developed a mouse model for inducible thyrocyte‐specific activation of BRAF V600E, which showed features similar to those of human papillary thyroid cancer. LSL‐Braf V600E ; Tg CreER T2 showed thyroid tumour development in the entire thyroid, and the tumour showed more abnormal cellular features with mitochondrial abnormalities in mice fed a high‐fat diet (HFD). Transcriptomics revealed that adrenomedullin2 ( Adm2 ) was increased in LSL‐Braf V600E ; Tg CreER T2 mice fed HFD. ADM2 was upregulated on the addition of a mitochondrial complex I inhibitor or palmitic acid with integrated stress response (ISR) in cancer cells. ADM2 stimulated protein kinase A and extracellular signal‐regulated kinase in vitro . The knockdown of ADM2 suppressed the proliferation and migration of thyroid cancer cells. We searched The Cancer Genome Atlas and Genotype‐Tissue Expression databases and found that increased ADM2 expression was associated with ISR and poor overall survival. Consistently, upregulated ADM2 expression in tumour cells and circulating ADM2 molecules were associated with aggressive clinicopathological parameters, including body mass index, in thyroid cancer patients. Collectively, we identified that ADM2 is released from cancer cells under mitochondrial stress resulting from overnutrition and acts as a secretory factor determining the progressive properties of thyroid cancer. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.